2011
DOI: 10.1167/11.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of attention to biological motion: Local motion dominates global shape

Abstract: Directional information can be retrieved from a point-light walker (PLW) in two different ways: either from recovering the global shape of the articulated body or from signals in the local motion of individual dots. Here, we introduce a voluntary eye movement task to assess how the direction of a centrally presented, task-irrelevant PLW affects the onset latency and accuracy of saccades to peripheral targets. We then use this paradigm to design experiments to study which aspects of biological motion-the global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…In all cases, they have been shown to influence task performance significantly, even when they were not recognized as biological (Wang et al, 2014) or when they were task-irrelevant (Bosbach et al, 2004;Hirai et al, 2011;Thornton & Vuong, 2004 In summary, there is evidence of congruency effects using motion stimuli. The first goal of the present experiments was to use other dot stimuli than already used in Bermeitinger (2013) to further investigate the positive-followed-by-negativecompatibility effects pattern found therein.…”
Section: Biological Motion In Congruency/compatibility Tasksmentioning
confidence: 83%
See 1 more Smart Citation
“…In all cases, they have been shown to influence task performance significantly, even when they were not recognized as biological (Wang et al, 2014) or when they were task-irrelevant (Bosbach et al, 2004;Hirai et al, 2011;Thornton & Vuong, 2004 In summary, there is evidence of congruency effects using motion stimuli. The first goal of the present experiments was to use other dot stimuli than already used in Bermeitinger (2013) to further investigate the positive-followed-by-negativecompatibility effects pattern found therein.…”
Section: Biological Motion In Congruency/compatibility Tasksmentioning
confidence: 83%
“…5). A comparable experiment was conducted by Hirai, Saunders, and Troje (2011). Participants saw a pointlight walker and a dot at each side of the walker.…”
Section: Biological Motion In Congruency/compatibility Tasksmentioning
confidence: 99%
“…It was recently found that local direction signals conveyed by feet-motion act as a pre-attentive feature in visual search tasks (Wang et al, 2010). Whereas walking direction may be judged from a basic pre-attentive local cue (Hirai, Saunders, & Troje, 2011;Wang, et al, 2010) information about gender-stereotypical gait patterns are found in the relation between hip and shoulder sway inherent in the global configuration of motion. In this view the non-decaying high precision VSTM of gait-direction, and features such as orientation and spatial frequency are all associated with pre-attentive local features.…”
Section: Discussionmentioning
confidence: 99%
“…Perception of biological motion relies on both global (Bertenthal & Pinto, 1994) and local processes (Troje & Westhoff, 2006;Hirai, Saunders, & Troje, 2011). Although global translational movement is absent when a point light walker is displayed as walking on a treadmill, direction can still be obtained by the recovery of motion defined shape of the walker, or by the local varying motions of individual dots (Hirai, Saunders, & Troje, 2011).…”
Section: Memory Of Biological Motionmentioning
confidence: 99%
See 1 more Smart Citation